LEARNING STYLES AND THEIR INFLUENCE ON ELEMENTARY SCHOOL STUDENTS’ MATHEMATICS LEARNING OUTCOMES - Atika Dwi Evitasari; Siwi Utaminingtyas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of learning styles on students’ mathematics learning outcomes at grade V elementary school. This study utilized an ex post facto method using an explanatory research design. This research was conducted at four public elementary schools in Desa Hargowilis, Kokap, Kabupaten Kulon Progo. The four elementary schools were: 1) SD Negeri Tegiri; 2) SD Negeri 1 Sremo; 3) SD Negeri 2 Sremo; dan 4) SD Negeri 3 Sremo. The research was conducted from March to May 2019. The population waa students of grade V at the public elementary schools in Desa Hargowilis. The sampling technique was purposive sampling, with a sample of 51 students. The instruments used in this study were questionnaire sheets and documentation. The data were analyzed by using descriptive analysis to describe the research variables, while the hypothesis was examined by applying the correlation and simple regression analysis. Based on the results of the study, it was concluded that learning styles had a significant effect on mathematics learning outcomes with t-count > t-table that was 6.115 > 1.676, with a correlation value of 0.658 meaning that there was a strong relationship and it contributed for 43.3%.